TRANSFORMASI SEBUAH TRADISI INTELEKTUAL: Asal Usul dan Perkembangan Pendidikan pada Masa Awal Sejarah Islam - Nasrul Hasan (POTENSIA: Jurnal Kependidikan Islam, 2016)
Transformation is any displacement of science, the intellectual activity, from teacher to student and so in the context of the growth and development of education in the early history of Islam. The purpose of this discussion to determine the form peralihanilmu and development of Islamic education in the early history of Islam. This writing method descriptive analysis. Discussion regarding the form of change and transition of science in the early history of Islam. Makkah period, the process of transition of knowledge from the companions of the Prophet to be done with the system dealing directly with the Prophet (musyafahah) .After the system says, memorizing and teaching returned as received from the teacher (talaqqi). Both systems are considered to be very tested and most noble among sistempendidikan that ever existed in the world of education. Medina period, is aimed more at political and social education and citizenship. The subject matter of this education is basic thoughts contained in the Charter of Medina and also the teaching of the Koran remains a priority